Penggunaan Terpadu Pupuk Hayati Bacillus-Nitrobacter dan Mikronutrisi dalam Mengurangi Hama Serangga Utama pada Padi - Khulaimi Khulaimi; Supriyadi Supriyadi; Retno Wijayanti (Universitas Lambung Mangkurat, 2026)
Paddy productivity is threatened by pests such as Cnaphalocrosis medinalis and Leptocorisa acuta that spread throughout the year. One possible solution is using Bacillus, Nitrobacter, and micronutrient biofertilizers to reduce leaffolders and rice bug infestation while enhancing the growth and yield of paddy. This research aimed to identify the effect of applying Bacillus, Nitrobacter, amino acids, and silica biofertilizers in controlling leaffolders and rice bug in paddy. The study was conducted in Segawe Backwoods, Purwosari Village, Wonogiri Sub-district, Wonogiri Regency, Central Java from April-August 2024. The method used was a single plot of 6 treatments with each treatment without replication, namely 100% chemical fertilizer, biofertilizers, biofertilizers + 25% chemical fertilizer, biofertilizers + 50% chemical fertilizer, biofertilizers + 75% chemical fertilizer, biofertilizers + 100% chemical fertilizer. Observation variables were population and intensity of pest attacks, population of Paederus fuscipes, level of parasitization, number of total tillers, number of productive tillers, and dry grain harvest production. The data analysis used was T-test. The results showed that the population and intensity of pest attacks tended to be lower in the combination treatment and higher in the 100% chemical fertilizer. The population of P. fuscipes was relatively high and always increased. The overall parasitization rate was 6,45%. Parasitoids found attacking C. medinalis in the research area were M.philippinensis and M.clathratus.The total number of tillers and productive tillers and dry grain harvest production was higher in combination treatment. The population of P. fuscipes was relatively high and always increased.